Uji Fitokimia dan Aktivitas Antijamur Ekstrak Teripang Keling (Holoturia atra) Dari Pantai Bandengan Jepara Terhadap Jamur Candida albicans - Septiadi, Tedi; Pringgenies, Delianis; Radjasa, Ocky Karna (977-2407769)
Holothuria atra is one of the marine lifes that lives at the bottom of the substrate, and able to adapt to its environment. Several previous studies showed that extracts of H. atra from different waters have activity as an antifungal. Fungus Candida albicans is one of human pathogens that attack on the mucosa of the mouth, skin and vagina. The purpose of this study were to identify the compounds contained in the extracts of H.atra and examine the effect of extracts concentration against C. albicans. The process of extraction was done by maceration with solvent n-hexane, ethyl acetate and methanol. Testing of secondary metabolites was carried out using phytochemical screening methods while testing antifungal activity was using agar diffusion test. The results showed that the extracts of H.atra contained saponins, alkaloids, steroids and triterpenoids. Antifungal activity assays showed that the n-hexane extract did not show any inhibition zone, while the ethyl acetate and methanol extracts showed inhibition zone at a concentration of 1 mg / disk with a large zone of inhibition of 8.27 Â± 0.06 and 8.07 Â± 0 , 12 mm, respectively based on these results it can be concluded that the extract of ethyl acetate solvent H.atra has strong potential as antifungal.